Gender Disparities, Complications, and Treatment Approaches in Insulin Resistance: Evidence from a Tertiary Care Center - Asma Omar; Sana Abdalrahman (AlQalam Journal of Medical and Applied Sciences, 2025)
Insulin resistance (IR) is a metabolic condition where the body's response to insulin is impaired, contributing to type 2 diabetes, obesity, and metabolic syndrome. This retrospective study at Al-Bayda Diabetes Center, Libya, included 67 patients diagnosed with IR from January 2023 to September 2024. The sample was predominantly female (90%) with a mean age of 43 years and mean BMI of 36 kg/m², indicating obesity. Statistical analysis showed moderate positive correlations between HbA1c and HOMA-IR (r = 0.63), and BMI and HOMA-IR (r = 0.41), reflecting the link between glycemic control, adiposity, and insulin resistance severity. About 69% of patients had complications, mainly obesity-related. Treatment mostly involved lifestyle interventions: 44.6% used diet and exercise, and 28.6% took dietary supplements; metformin was less commonly prescribed. The findings highlight the importance of managing obesity and glycemic levels in IR treatment, with lifestyle modification as the primary approach. The predominance of female patients suggests potential gender-related differences in IR prevalence that need further study.